2010
DOI: 10.1016/j.ijbiomac.2009.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extraction conditions on properties of seed xyloglucan

Abstract: Xyloglucans are water-soluble polysaccharides that serve as storage in cotyledonary tissues from seeds of Hymenaea courbaril among other Leguminosae. The use of xyloglucans is dependent on their solution properties. We now examine the influence of different times of extractions on its properties. Xyloglucans were obtained from milled and defatted cotyledons of H. courbaril by aqueous extraction at 25 degrees C for 0.25, 0.5, 1, 5, 15, 24, and 48 h. Composition data showed that increase in time lead to the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
4
9
1
Order By: Relevance
“…The branching pattern of xyloglucan from different plant species was evaluated and demonstrated that some xyloglucans have an additional arabinose unit linked to the galactose residues at the non-reducing end of the side chain [31]. Kay & Petkowicz [25] suggest that the presence of arabinose is due to co-purified arabinan, which corroborates our result. They also confirmed the absence of arabinose residues in shorter extraction processes, while others workers [3,11] described arabinose traces in xyloglucans from seeds.…”
Section: Monosaccharide Compositionsupporting
confidence: 89%
See 4 more Smart Citations
“…The branching pattern of xyloglucan from different plant species was evaluated and demonstrated that some xyloglucans have an additional arabinose unit linked to the galactose residues at the non-reducing end of the side chain [31]. Kay & Petkowicz [25] suggest that the presence of arabinose is due to co-purified arabinan, which corroborates our result. They also confirmed the absence of arabinose residues in shorter extraction processes, while others workers [3,11] described arabinose traces in xyloglucans from seeds.…”
Section: Monosaccharide Compositionsupporting
confidence: 89%
“…No signals ascribed to non-reducing ␤-arabinofuranosyl units were observed at 109/5.3 ppm. This type of residue was reported in other plant polysaccharide [25]. They may occur only in minor amounts in our xyloglucan preparation and not detected on the NMR spectrum.…”
Section: Nuclear Magnetic Resonance Spectroscopysupporting
confidence: 74%
See 3 more Smart Citations